2018
DOI: 10.1371/journal.ppat.1007308
|View full text |Cite
|
Sign up to set email alerts
|

NLRP6 negatively regulates pulmonary host defense in Gram-positive bacterial infection through modulating neutrophil recruitment and function

Abstract: Gram-positive bacteria, including Staphylococcus aureus are endemic in the U.S., which cause life-threatening necrotizing pneumonia. Neutrophils are known to be critical for clearance of S. aureus infection from the lungs and extrapulmonary organs. Therefore, we investigated whether the NLRP6 inflammasome regulates neutrophil-dependent host immunity during pulmonary S. aureus infection. Unlike their wild-type (WT) counterparts, NLRP6 knockout (KO) mice were protected against pulmonary S. aureus infection as ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 53 publications
9
113
0
Order By: Relevance
“…Our data and the findings reported by Brandes et al (8) support the view that early engagement of neutrophils instigates a damaging feedforward innate inflammatory circuit responsible for severe disease development following IAV infection. Neutrophils are the first responders to infiltrate the sites of infection to clear bacterial infections (37,38). In this regard, enhanced tissue neutrophil apoptosis caused by BCL6 deficiency may increase pulmonary bacterial burden and worsen outcome during certain respiratory bacterial infections, such as Staphylococcus pneumonia infection (37,38).…”
Section: Bcl6 Represses Apoptotic Gene Expression In Neutrophils Specmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data and the findings reported by Brandes et al (8) support the view that early engagement of neutrophils instigates a damaging feedforward innate inflammatory circuit responsible for severe disease development following IAV infection. Neutrophils are the first responders to infiltrate the sites of infection to clear bacterial infections (37,38). In this regard, enhanced tissue neutrophil apoptosis caused by BCL6 deficiency may increase pulmonary bacterial burden and worsen outcome during certain respiratory bacterial infections, such as Staphylococcus pneumonia infection (37,38).…”
Section: Bcl6 Represses Apoptotic Gene Expression In Neutrophils Specmentioning
confidence: 99%
“…Neutrophils are the first responders to infiltrate the sites of infection to clear bacterial infections (37,38). In this regard, enhanced tissue neutrophil apoptosis caused by BCL6 deficiency may increase pulmonary bacterial burden and worsen outcome during certain respiratory bacterial infections, such as Staphylococcus pneumonia infection (37,38). Conversely, excessive neutrophil recruitment is a hallmark of acute susceptibility to Mycobacterium tuberculosis and is associated with overexuberant inflammatory response and disease progression (39).…”
Section: Bcl6 Represses Apoptotic Gene Expression In Neutrophils Specmentioning
confidence: 99%
“…Thus, it is unique in the NLR family as it can perform functions of both NLRs and TLRs. 10 This notion is supported by other studies proposing a wide scope of physiological functions of Nlrp6 ranging from modulation of the host-microbial interface 11 and host defense against pathogens 12,13 to inhibition of carcinogenesis 14 and neuroinflammation. 15 However, Nlrp6 has also been shown to negatively regulate NF-κB signaling in mouse model.…”
Section: Nod-like Receptors In Immunitymentioning
confidence: 57%
“…Recently, we 12 and others 18 reported that the Nlrp6 inflammasome is activated during bacterial infections. In our study, Nlrp6 −/ − bone marrow-derived macrophages (BMDMs) showed reduced caspase-1 processing and IL-β secretion compared to that of WT BMDMs when infected with methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Nlrp6 Assembles An Inflammasomementioning
confidence: 92%
See 1 more Smart Citation